Mapping of dental graduates’ career paths in Hong Kong, Japan and mainland China - Jiang, Chloe Meng; Nishioka, Takashi; Hong, Guang; Yu, Hao; Zhang, Chang-yuan; Chu, Chun Hung (Frontiers in Oral Health, 2022)
Dental graduates have a variety of career-path choices. After graduation, they may join private dental practice, government- or hospital-based dental care services, research groups, academia, business or industry. With globalization and frequent international exchange, dental graduates nowadays can explore careers outside their home country. However, dental education systems and job opportunities vary widely across different regions and countries. Diversity of accreditation in dental education, different licensure requirements, and lack of global competencies in dental care often limit the globalization, operation and survival of dental practice and education worldwide. The requirements for professional education and practice can be quite diverse, and these differences will be barriers to dental graduates seeking career development outside their home home country. Fresh dental graduates have minimal experience in job hunting. More specifically, they are unfamiliar with potential career paths. This paper was based on the 4th trilateral symposium 2022 organized by The University of Hong Kong, Tohoku University, and Fujian Medical University, which offered a lecture to discuss career paths for dental graduates in Hong Kong, Japan, and mainland China. The aim of this paper was to provide dentists, particularly fresh graduated dental students, with practical insight into different career paths in Hong Kong (Special Administrative Region of China, SAR), Japan and mainland China, and factors that may influence their career options. It assists dental students in exploring possibilities in dentistry and preparing for their career development after graduation from dental school.